Navigating parenting challenges: A qualitative study of communication experiences among young Chinese couples facing breast cancer while raising underage children - Yingchun Li; Meichan Chong; Pinglei Chui; Lin Mo; Liande Tao; Yuman Yuan; Qiaoli Zhong; Maoting Tang; Yanjia Liu (PLoS ONE, 2026)
This qualitative study aimed to gain an in-depth understanding of the communication experiences of young couples with breast cancer as they navigate the challenges of raising underage children. Semi-structured interviews were conducted with 13 couples with breast cancer recruited through purposive sampling in the inpatient ward of a tertiary hospital in Sichuan Province, China. The interviews, conducted face-to-face between May 2024 and June 2024, were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. This study was guided by the Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist. Two researchers independently coded the data using NVivo 12.0, developing major themes and subthemes through an inductive process and constant comparison. The analysis revealed two main themes, each encompassing three to four subthemes. The first theme, dyadic coparenting through constructive communication: a shared journey of navigating parenting challenges, which includes open communication of parenting experiences, emotional co-regulation in parenting, and positive communication of parenting plans; The second theme, negative co-parenting communication: protect parenting emotions or not provide emotional support, which includes “instrumental support” and emotional avoidance, avoid communication to prevent emotional fluctuations, communication concealment to avoid increasing parenting pressure, and invalid communication without providing parenting emotional support. These findings highlight the diverse communication strategies employed by young couples with breast cancer in parenting their underage children. The study underscores the need for healthcare professionals to develop targeted interventions to enhance communication between young breast cancer couples, with the aim of improving their ability to co-parent effectively during this challenging time.